Evaluasi dan Penetapan Harga Pokok Produk pada PT. Pos Indonesia (Persero) dengan Metode Time Driven Activity Based Costing Jasa Pengiriman Paket Dalam Negeri Kantor Pos Indonesia Meulaboh - Navisah Navisah; Ahmad Arkadius (PENG: Jurnal Ekonomi dan Manajemen, 2025)
For PT. package delivery services. Pos Indonesia is able to facilitate domestic and international deliveries with a variety of services. However, competitors PT. Pos Indonesia, especially for its own package services, also competes by offering a variety of services to consumers. From the description above, the problem formulation is how to evaluate and determine the cost of products at PT. Pos Indonesia (Persero) using the time driven activity based costing method for domestic package delivery services at the Indonesian Post Office, Meulaboh, the research objectives that the author wants to achieve in this research are: to find out the evaluation and determination of product cost prices at PT. Pos Indonesia (Persero) using the time driven activity based costing method for domestic package delivery services at the Indonesian Post Office, Meulaboh. The data analysis method used in this writing uses a qualitative method, namely the data that has been collected is then discussed with the support of several expert opinions as a theoretical basis for drawing conclusions about the problems faced. From the table above, the average of respondents who answered strongly agree was 43.34, who answered agree was 42.67, who answered neutral was 4.67, who answered disagree was 6.67 and who answered strongly disagree was 2.67. So it can be said that evaluating and determining the basic price of products at PT. Pos Indonesia (Persero) using the time driven activity based costing method, domestic package delivery services at the Meulaboh Indonesian Post Office is good, where S+ SS > STS + TS means the hypothesis is accepted.